2017
DOI: 10.1021/acschemneuro.7b00297
|View full text |Cite
|
Sign up to set email alerts
|

Neurodegenerative Disease Proteinopathies Are Connected to Distinct Histone Post-translational Modification Landscapes

Abstract: Amyotrophic lateral sclerosis (ALS) and Parkinson's disease (PD) are devastating neurodegenerative diseases involving the progressive degeneration of neurons. No cure is available for patients diagnosed with these diseases. A prominent feature of both ALS and PD is the accumulation of protein inclusions in the cytoplasm of degenerating neurons; however, the particular proteins constituting these inclusions vary: the RNA-binding proteins TDP-43 and FUS are most notable in ALS, while α-synuclein aggregates into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 89 publications
4
32
0
Order By: Relevance
“…One important question is the molecular mechanism underlying the decrease in histone acetylation observed in Tg FUS +/+ mice. ALS-causative genes have been associated with various epigenetic modifiers and epigenetic tags [7, 12]. For example, the DNA/RNA binding protein FUS directly interacts with CBP and p300, two histone acetyltransferases, as well as with HDAC1 [72, 73].…”
Section: Discussionmentioning
confidence: 99%
“…One important question is the molecular mechanism underlying the decrease in histone acetylation observed in Tg FUS +/+ mice. ALS-causative genes have been associated with various epigenetic modifiers and epigenetic tags [7, 12]. For example, the DNA/RNA binding protein FUS directly interacts with CBP and p300, two histone acetyltransferases, as well as with HDAC1 [72, 73].…”
Section: Discussionmentioning
confidence: 99%
“…These alterations comprise changes in phosphoacetylation of serine 10 and lysine 14 on the H3 tail (H3K14ac-S10ph), dimethylation of lysine 4 on the H3 tail (H3K4me2), and trimethylation of lysine 9 on the H3 tail (H3K9me3) ( Jimenez-Pacheco et al, 2017 ; Masala et al, 2018 ). It has also been shown that FUS can abrogate histone 4 (H4) methylation in arginine residues by inhibiting methyltransferase PRMT1 ( Tibshirani et al, 2015 ), and that overexpression of human FUS in yeast diminishes H3 acetylation in two different residues, lysine 14 and lysine 56 (H3K14 and H3K56) ( Chen K. et al, 2018 ). In addition, FUS was shown to inhibit CBP/p300 HAT after binding to it, leading to a hypoacetylation state ( Alao, 2007 ; Wang et al, 2008 ).…”
Section: Regulation Of Neurogenic Function In Als Through Epigenetic mentioning
confidence: 99%
“…Additionally, histone H3/H4 tetramer is extracted as a single, pure, and abundant fraction, enabling a reliable quantification of preserved PTMs on each of the proteins. PTMs are extremely sensitive to changes in oxidative stress and changes in pH 20,21 . Thus, in contrast to previously published methods 18 , we report an efficient strategy of rinsing the cells in serum-free media to ensure a minimum metabolic disturbance of the cells and to avoid the interference of the native PTMs with serum components.…”
Section: Discussionmentioning
confidence: 99%